A Role of AI in Personalized Health Care and Medical Diagnosis - Purohit, Abhay; Gautam, Kamlesh; Kumar, Sameer; Verma, Shivam (International Journal of Psychosocial Rehabilitation, 2020)
Artificial intelligence is often portrayed as evil robots ready to take over the world but we’re here to make the case that AI can literally save the lives of millions of patients around the world and improve healthcare with tools decide on an accurate delivery. It can have a computer model that, based on the experience of thousands of other patients, knows whether a treatment will work, and based on what is best for that patient and their individual circumstances. AI enables us to gain a deeper and more comprehensive understanding of human health than we had before. Medical software has consisted of medical devices also known as AI-based software for diagnosing, treating or treating diseases such as invasive surgery, or most software with the same effect, whenever used by a patient or physicians’ role. No matter how many times we use it. In other words, AI software behaves very differently from most software in healthcare due to its inherent ability to learn and evolve overtime, ideally intelligently large enough to fit the predictors of the context in which it is used and improving health outcomes.